Carmen Based on a Novel by Prosper Mérimée - Riesenfeld, Hugo; Mérimée, Prosper (Lobster Films, 2014)
Carmen was an early film in Cecil B. DeMille's Hollywood career. It features everything that he was good at: crowds, fights, over-the-top emotions and unhinged behavior. It is also considerably leaner than his later, more bloated features. Geraldine Farrar was an internationally renowned operatic soprano. War and a tired voice brought her to motion pictures. Any worries that she would overact with operatic gestures were quickly allayed. Farrar's down-to-earth personality came through and her performance was very natural for the period. She was not a classic beauty but her features were intriguing, her body language is mesmerizing and she is convincing as the sexy Carmen. [moviessilently.com]